2021
DOI: 10.15575/jtk.v6i1.12603
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Learning Style on Students’ Learning Performance During the Covid-19 Pandemic

Abstract: The research aims to determine the effect of learning style on students’ performance through online learning during the Covid-19 pandemic. The subjects of study are 269 chemistry education students at three universities in Indonesia. The data collection of learning style uses a Likert scale questionnaire, and learning performance is obtained from students’ grade point average. In this research, students’ learning style was divided into visual, auditorial, and kinesthetic. Data were analyzed using descriptive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…> 0.050. Learning styles influence learning result, but differences in learning techniques in students do not significantly affect mastery of learning concepts, learning styles simultaneously or separately can affect students learning achievement (Albeta et al, 2021). Furthermore, the results of other studies show that the more following the learning style with the personality of the learners, the higher the achievement of students (Chetty et al, 2019;Cimermanová, 2018;Nurmalasary, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…> 0.050. Learning styles influence learning result, but differences in learning techniques in students do not significantly affect mastery of learning concepts, learning styles simultaneously or separately can affect students learning achievement (Albeta et al, 2021). Furthermore, the results of other studies show that the more following the learning style with the personality of the learners, the higher the achievement of students (Chetty et al, 2019;Cimermanová, 2018;Nurmalasary, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Every student has all three learning styles, and it is just that one style that is usually more domineering (Priya et al, 2020). A teacher must inform each student about their learning style so that they can help use the right learning media for teaching and learning activities (Albeta et al, 2021;Li et al, 2016). In the activities of the learning process in the classroom there are some students who prefer the teacher to explain the material by writing everything in detail on the blackboard so that they can read it and then process it to understand it.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition, various audio, visual, and audio visual media can facilitate students' diverse learning styles. Bobbi DePorter said that students' learning styles consist of 3 types, namely visual, auditory and kinaesthetic (Albeta et al, 2021;Nur Kholis, 2016). How to learn children with visual learning styles pay more attention to explanations made using pictures or eye contact about what being studied (Jongerius et al, 2020;Kartika et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This type of student generally likes to revise materials and use books or summaries as a favourite tool for collecting data and sharing information [17]; 4) Kinesthetic (K). Pei-Xin [8] and Albeta [18] define a kinesthetic learner as an individual who learns with much movement or learns by direct experimenting.…”
Section: Fleming-mills Vark Modelmentioning
confidence: 99%
“…Although this is true, it should also be considered that the impact of learning style on academic achievement may differ from one study to another. For example, Albeta et al [18] found that visual and kinesthetic learning styles have lower performance than aural learning styles. In comparison, Zain et al [10] concluded that students who obtained high academic scores were those who used kinesthetic learning styles based on their research on students in Selangor.…”
Section: The Relationship Between Learning Style and Academic Achieve...mentioning
confidence: 99%